Customer Satisfaction and Loyalty Management of Bank Sahabat Sampoerna Branch Kelapa Gading - Wahid Akbar Basudani; Valentine Theresia Simamora; Gani Wiharso; Muhammad Abdullah; Hary Mulyadi (Jurnal Mandiri : Ilmu Pengetahuan, Seni, dan Teknologi, 2022)
The purpose of this study is to determine whether there is an effect of service quality, customer motivation and customer behavior on customer satisfaction with customer complaints as moderation and its impact on customer loyalty at Bank Sabahat Sampoerna Branch Kelapa Gading This study uses the SEM method with the Smart-PLS application. The number of samples in this study amounted to 52 with the sampling technique of accidental sampling which is included in the type of non-probability sampling where the object in this study is the customer who uses credit facilities at Bank Sahabat Sampoerna Branch Kelapa Gading. The results of this study obtained the endogenous variable Customer Satisfaction (Y) of 0.98 and Customer Loyalty (Z) of 0.97. This indicates that the endogenous latent variable Customer Satisfaction (Y) is strongly influenced by the exogenous variables of Service Quality (X1), Customer Motivation (X2) and Customer Behavior (X3). Meanwhile, the endogenous latent variable of Customer Loyalty (Z) is strongly influenced by 0.97 by the exogenous variables of Service Quality (X1), Customer Motivation (X2) and Customer Behavior (X3) through the mediating variable of Customer Satisfaction (Y).